The menopausal syndrome. Issue 2 (May 1974) - McKinlay, Sonja M.; Jefferys, Margot
Abstract : Results of a postal questionnaire survey of 638 women aged 45 to 54, living in the London area in 1964-65, indicate (consistently with other recent surveys) that hot flushes and night sweats are clearly associated with the onset of a natural menopause and that they occur in the majority of women. Hot flushes were reported to occur more frequently (usually daily) and over more of the body by women whose menstrual flow showed evidence of change or cessation, and for 25% of those women whose menses had ceased for at least one year, hot flushes persisted for five years or more. The other six symptoms specified, namely, headaches, dizzy spells, palpitations, sleeplessness, depression, and weight increase, showed no direct relationship to the menopause but tended to occur together, each being reported by approximately 30 to 50% of the respondents with little variation according to menopausal status. None of the six sociodemographic variables investigated, i.e., employment status, school leaving age, social class, domestic workload, marital status, and parity, had any marked association with the reported frequency of symptoms. The majority of respondents did not anticipate or experience any difficulties and only about 10% expressed regret at the cessation of menses. Despite embarrassment and/or discomfort from hot flushes, reported by nearly three-quarters of those experiencing this symptom, only one-fifth had apparently sought medical treatment.